Urgensi Penyiaran Misa Online bagi Orang Muda Katolik Gereja Katedral Santo Petrus Bandung - Alfonso Hedo Yehudatama; Bernardus Ario Tejo Sugiarto (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2025)
The Saint Peter's Cathedral in Bandung has continued to broadcast Mass online, both daily and weekly, through the YouTube account of the Communications Commission of the Archdiocese of Bandung, even in the post-COVID-19 pandemic period. After the pandemic, congregants have been allowed to attend Mass in person at the church. Consequently, the online Mass broadcasts from Saint Peter's Cathedral have lost the urgency they once held during the pandemic. Is the online broadcasting of Mass still necessary for the faithful? The researcher has selected the Youth Catholic Community (OMK) at Saint Peter's Cathedral as the subject of the study. This group primarily consists of Generation Z, known for their familiarity with the internet and digital environments. Generation Z is generally more comfortable in the virtual realm than in the physical one. The research employs a quantitative methodology, with data collected via an e-questionnaire using Google Forms, which was distributed to OMK members through WhatsApp. The hypothesis of this study posits that OMK, as representatives of Generation Z, prefer online Mass over in-person attendance.AbstrakGereja Katedral Santo Petrus Bandung di paska pandemi Covid-19 masih menyiarkan misa secara online, baik harian dan mingguan melalui akun Youtube Komisi Komsos Keuskupan Bandung. Di paska pandemi Covid-19, umat sudah diperkenankan hadir kembali merayakan misa di Gereja. Dengan demikian, misa online yang disiarkan Gereja Katedral Santo Petrus Bandung telah kehilangan urgensinya seperti yang ada pada masa pandemi. Apakah penyiaran misa online masih diperlukan oleh umat? Untuk menjawab pertanyaan ini, peneliti memilih OMK (Orang Muda Katolik) di Gereja Katedral Santo Petrus Bandung sebagai subjek penelitian, karena OMK saat ini termasuk di dalam Generasi Z yang dikenal sebagai Generasi Internet dan Generasi Digital. Generasi Z lebih akrab dengan dunia virtual, dibandingkan dengan dunia real. Metode penelitian yang digunakan adalah penelitian kuantitatif. Peneliti mengumpulkan data melalui e-kuesioner menggunakan aplikasi G-form dan disebarkan kepada OMK melalui WhatsApp. Hipotesis penelitian ini adalah OMK sebagai perwakilan Generasi Z lebih menyukai misa online dibandingkan misa offline.